Electro-Kinetic Treatment (EKT) on Reinforced Peat with Nylon Fiber for the Sub-grade Layer Strengthening. - Norazzlina, M.Sa’don; Abdul Razak, Abdul Karim; Emilia Evelyn, Christermaller; Mohamad Hanif, Mohamad Ariffin; Albert Akun, Merang (Universiti Malaysia Sarawak, 2018)
Peat consists of the highly organic substance that derived primarily from plant material which is form when decomposed plant/animals accumulate more quickly than it humidifies. Peat possesses low strength, low bearing capacity and easily undergo differential and total settlement and recorded the highest moisture content (200-2200%) among all the soils. Therefore, it is crucial to enhance stability, increase bearing capacity, and reduce excessive settlement as well as lateral deformation to support and improve any structure and/or infrastructure build on peat. This study focused on investigating the strength increment of peat in natural and dry state mixed as sub-grade layer with various percentages (0.3%, 0.5%, and 0.8%) of nylon fiber (NF) as reinforcement, 5% cement as binder and later the treated peat were applied to the electrokinetic treatment (EKT) for further enhancing the compressive strength. The nylon fiber is chosen due to its very strong characteristic with extremely resistant to abrasion and bending. It is lightweight with the specific gravity of 1.04 and durability properties make nylon fiber an ideal reinforcement material. The nylon fiber varies from 10 mm to 50 mm length sizes and is a product from the tire waste disposal (extracted from car type). The peat samples collected are categorized as Sapric peat (H7) with recorded moisture content of 425%. The development of the compressive strength was determined by using Unconsolidated-Undrained (UU) Triaxial test for natural state, Unconfined Compressive Strength (UCS) test and California Bearing Ratio (CBR) test are at drying state. All samples were air-cured for 7 days, 14 days and 28 days. The application of EKT was practiced with 3.0 V and 12 V applied for 10 minutes duration for UU/UCS and CBR, respectively. From the preliminary results obtained (Figure 1), the treated peat using nylon fiber and electro-kinetic treatment has improved significantly the compressive strength of the treated peat for both natural and dry state when compared to non-treated peat.